Cold Start: The Cat is Out of the Bag - Dr. Naeem Salik (CISS Insight Journal, 2016)
After years of denial, despite sufficient evidence to the contrary, India finally seems to be moving towards a formal embrace of the Cold Start Doctrine. The new Indian Army Chief General Bipin Rawat has acknowledged the existence of this provocative war fighting doctrine and has urged his institution to gear up for its implementation. Western media, think tank wizards, academic scholars and security analysts had been lecturing Pakistan that its concerns about the Cold Start are misplaced because it exists more in Pakistani fantasies than in reality and that it had never been adopted officially either by the Indian military or the Indian government. The Manmohan government had indeed studiously avoided discussing this doctrine publicly though it let the Indian military war game it year after year starting in 2004. It is yet not clear what has really motivated General Rawat to open this can of worms early in his tenure. It seems that taking a cue from the belligerent stance of the BJP government towards Pakistan and a fire-breathing Defense Minister like Manohar Parrikar, the general might have seen a propitious opportunity to gain a formal government approval for Cold Start and with it a bigger chunk of resources. At the same time Rawat is also threatening Pakistan with surgical strikes though it is not part of the Cold Start menu.